KEPEMIMPNAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN TAHFIDZ AL-QUR’AN DI SD IT IQRA’ MEDAN - Umairoh, Bella; Hasibuan, Rizka (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2023)
The aim is to find out and analyze the leadership style and strategies of school principals in improving the quality of tahfidz Al-Qur'an learning, as well as knowing the supporting and inhibiting factors in implementing strategies to improve the quality of tahfidz Al-Qur'an learning at SD IT Iqra' Medan. This type of research uses qualitative research with a variety of approaches to what happens at SD IT Iqra' Medan. The data collection technique uses interviews, observation and documentation. The data analysis technique used is firstly by presenting the data, secondly by data reduction, thirdly by drawing conclusions. The results of this research show that; First, the leadership style used by the principal of SD IT Iqra' Medan is a democratic leadership style. Second, the leadership strategy provides special approaches to teachers and students. Third, there are several supporting factors in implementing the strategy created, such as teachers who have a high enthusiasm for teaching, a comfortable and conducive memorization location and support from the students' parents. Apart from that, there is also an inhibiting factor, namely students' limitations in memorizing.